Examining Nursing Students' Experiences Studying English As A Foreign Language: Problems And Ways To Cope - Imtihan Hanim (JOLADU: Journal of Language Education, 2026)
Every person must be able to speak English in order to facilitate community contact in the age of globalisation. English has become crucial for nurses to be able to compete in the age of globalisation and provide the best means of preventing communication misunderstandings. This study's goal is to examine the problems encountered and the ways to cope its problems English for Fourth semester Nursing students on at Poltekkes Banten. Based on the results, it is revealed that the most problems faced by the nursing students are lack of vocabulary, low self-esteem, shyness, and occasionally poor grammatical understanding can cause pupils to struggle when speaking English in class. Their ways or strategies to cope speaking problems cover get many internet source to access English learning video which cover dialogue, monologue and other digital form or online application, making note some unknown vocabularies to be translated into Bahasa, by doing something pleasant such as listening song, reading book and watching movie.